Development of novel potent ligands for GPR85, an orphan G protein‐coupled receptor expressed in the brain. (1st March 2022) - Sakai, Aya; Yasui, Takeshi; Watanave, Masashi; Tatsumi, Rine; Yamamoto, Yoshihiko; Takano, Wataru; Tani, Yuki; Okamura, Izumi; Hirai, Hirokazu; Takeda, Shigeki
Abstract: GPR85 is a member of the G protein‐coupled receptor and is a super‐conserved receptor expressed in the brain sub‐family (Super Conserved Receptor Expressed in Brain; SREB) with GPR27 and GPR173. These three receptors are "orphan receptors"; however, their endogenous ligands have not been identified. SREB has garnered the interest of many scientists because it is expressed in the central nervous system and is evolutionarily conserved. In particular, brain mass is reported to be increased and learning and memory are improved in GPR85 knockout mice (Matsumoto et al. 2008). In this study, we characterized newly synthesized compounds using a GPR85‐Gsα fusion protein and the [ 35 S]GTPγS binding assay and identified novel GPR85 inverse‐agonists with IC50 values of approximately 1 μM. To analyze the neurochemical character of the compounds and investigate the physiological significance of GPR85, we used cerebellar Purkinje cells expressing GPR85 and an electrophysiological technique. Based on the results, the inverse‐agonist compound for GPR85 modulated potassium channel opening. Together with the results of previous gene analysis of GPR85, we expect that the development of the GPR85 ligand will provide new insights into a few types of neurological disorders. Abstract : A GPR85 inverse‐agonist is possible to expect to improve learning and memory. We developed potent GPR85 inverse‐agonist and showed the compound modulated potassium channel opening.